ETIKA PENGGUNAAN AI DALAM DUNIA PENDIDIKAN UNTUK GURU PAUD (HIMPAUDI) KABUPATEN KUBU RAYA - Reza Maulana; Yoki Firmansyah; Lisnawanty; Ali Mustopa (Universitas Bina Sarana Informatika, 2025)
This community service activity aims to improve ethical literacy in the use of Artificial Intelligence (AI) technology in Early Childhood Education (PAUD) environments, particularly in Kubu Raya Regency. Based on observations, PAUD teachers who are members of HIMPAUDI Kubu Raya still face challenges in understanding the principles of ethics, privacy, and security of children's data when using AI-based technology in learning. This program offers gradual training consisting of three levels: basic (introduction to AI and ethics), intermediate (identifying safe and appropriate AI applications), and advanced (responsible AI implementation strategies). The training is complemented by case studies, discussions of ethical issues, mentoring, and facilitation of the development of contextual guidelines based on local values. In addition, a community of practitioners is formed as a collaborative forum for teachers to share experiences and solutions. The activity outputs include increased understanding of AI ethics, the ability to select safe applications, activity documentation, scientific and popular publications, and improved quality of PAUD learning that supports holistic child development. This program is expected to encourage the creation of a culture of ethical and wise use of AI among PAUD educators.